HMGB1 as a biomarker for myeloproliferative neoplasm complicated with atherosclerosis - Lunbi Wu; Dongxue Han; Xiaodong Zhang; Shixu Zhang; Yicong Wang; Wenxue Han; Bowen Jiang; Huailei Chen; Libo Jiang (European Journal of Medical Research)
Abstract Objective The study analyzed the relationship between serum levels of HMGB1 and biochemical indices related to atherosclerosis, clarifying the diagnostic value of HMGB1 in cases of myeloproliferative neoplasm (MPN) accompanied by atherosclerosis (AS). Methods The bone marrow samples and serum were obtained from patients with MPN. qPCR was used to detect the level of HMGN1 mRNA in bone marrow mononuclear cells, while ELISA was used to measure the level of HMGB1 in serum. Additionally, relevant biochemical indices of the patients were collected and the correlation between these indices and HMGB1 levels was assessed. Results Compared with the control group, MPN patients exhibited significantly elevated levels of HMGB1 in both bone marrow mononuclear cells and serum. The Pearson correlation analysis revealed a negative correlation between serum HMGB1 levels and both HDL-C and ApoA1. The ROC curve analysis demonstrated that serum HMGB1 had an AUC of 0.929 (P < 0.001) for predicting the complication of AS in MPN patients, with a sensitivity of 100.00% and a specificity of 78.05%. Furthermore, logistic regression analysis showed that serum HMGB1 levels were statistically significant in determining the presence of AS in MPN patients (P < 0.05). Conclusion Elevated levels of HMGB1 in the bone marrow and serum of MPN patients demonstrate a correlation with biochemical indices related to AS. This finding may serve as a valuable reference for predicting AS complications in MPN patients.